Impact of green bond issuance on company stock prices : A comparative study between emerging markets and advanced economies. - Asiala, Antti (My University, 2024)
This research paper aims to investigate the effects of corporate green bond issuance on the issuer’s stock price around the announcement of the event in two different samples. The two samples are specified according to the International Monetary Fund’s specification of advanced economies and emerging markets and developing economies. Both sample groups include 87 green bond issuances by listed companies during the observation period. The empirical analysis is carried out as an event study with corporate green bond announcement dates as the event date. The bond data is derived from the Bloomberg fixed-income database and includes 87 bond issuances for each of the two samples. I find that companies in advanced economies experience a slightly negative average CAR during the event window and their peers in emerging markets show an average CAR close to zero but slightly positive for the longer event windows. In addition, contradicting previous literature, matured issuers seem to have a more positive stock price reaction than first-time issuers of green bonds.

Tämä pro-gradu tutkielma tutkii yritysten vihreiden ns. ”green bond” joukkovelkakirjalainojen liikkeeseenlaskun vaikutuksia liikkeelle laskevan yhtiön osakekurssiin liikkeelle laskun julkistusajankohtana kahdessa eri kohderyhmässä. Kohderyhmät on jaoteltu listattuihin osakeyhtiöihin, jotka ovat laskeneet liikkeelle green bondeja Kansainvälisen valuuttarahaston (IMF) määrittelemissä kehittyneissä talouksissa ja kehittyvissä markkinoissa ja kehitysmaissa mukaan (eng. Advanced Economies ja Emerging Markets and Developing Economies EMDEs). Empiirinen analyysi suoritetaan tapahtumatutkimuksena, jossa tarkastellaan green bondien ilmoittamispäiviä tapahtumapäivinä. Joukkovelkakirjojen data saadaan Bloombergin fixed income -tietokannasta, ja tutkimuksessa tarkastellaan yhteensä 87: ntä joukkovelkakirjalainojen liikkeeseenlaskua kummassakin kohderyhmässä. Empiirisen tutkimuksen tulokset osoittavat, että kehittyneiden talouksien yrityksillä on tapahtumaikkunassa hieman negatiivinen keskimääräinen kumulatiivinen poikkeama (CAR) keskiarvosta, kun taas kehittyvillä markkinoilla yritysten osakekurssit reagoivat keskimäärin neutraalisti, mutta hieman positiivisesti pidemmissä tapahtumaikkunoissa. Lisäksi aiempaan tutkimukseen nähden tulokset osoittavat, että kokeneemmilla, jo aikaisemmin vihreitä joukkovelkakirjalainoja liikkeeseen laskeneilla yrityksillä on positiivisempi osakekurssireaktio verrattuna ensimmäistä kertaa vihreitä joukkovelkakirjalainoja liikkeeseen laskeneisiin yrityksiin.
Keywords: bonds; green economy; security market; sustainable development; emerging markets; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; Master's Degree Programme in Finance